Integrated single-base resolution maps of transcriptome, sRNAome and methylome of Tomato yellow leaf curl virus (TYLCV) in tomato - Piedra-Aguilera, Álvaro; Jiao, Chen; Pérez-Luna, Ana Isabel; Villanueva, Francisco; Dabad, Marc; Esteve-Codina, Anna; Diaz-Pendón, Juan Antonio; Fei, Zhangjun; Rodríguez-Bejarano, Eduardo; Castillo-Garriga, Araceli (Springer Nature, 2019)
Geminiviruses are plant ssDNA viruses that replicate through dsDNA intermediates and form minichromosomes which carry the same epigenetic marks as the host chromatin. During the infection, geminiviruses are targets of the post-transcriptional and transcriptional gene silencing machinery. To obtain insights into the connection between virus-derived small RNAs (vsRNAs), viral genome methylation and gene expression, we obtained the transcriptome, sRNAome and methylome from the geminivirus Tomato yellow leaf curl virus-infected tomato plants. The results showed accumulation of transcripts just at the viral ORFs, while vsRNAs spanned the entire genome, showing a prevalent accumulation at regions where the viral ORFs overlapped. The viral genome was not homogenously methylated showing two highly methylated regions located in the C1 ORF and around the intergenic region (IR). The compilation of those results showed a partial correlation between vsRNA accumulation, gene expression and DNA methylation. We could distinguish different epigenetic scenarios along the viral genome, suggesting that in addition to its function as a plant defence mechanism, DNA methylation could have a role in viral gene regulation. To our knowledge, this is the first report that shows integrative single-nucleotide maps of DNA methylation, vsRNA accumulation and gene expression from a plant virus.
Keywords: Virus fitopatógenos; Tomates - Enfermedades y plagas; TYLCV; methylome; transcriptome; sRNAome; tomato